Torsional behaviour of rectangular high-performance fibre-reinforced concrete beams. (January 2022) - Karimipour, Arash; de Brito, Jorge; Ghalehnovi, Mansour; Gencel, Osman
Abstract: This study intends to compare the influence of polypropylene fibres (PPF) and steel fibres (SF) on the torsional performance of reinforced high-performance concrete (HPC) rectangular beams. Nine reinforced HPC beams were produced and tested under a torsion load. All specimens were designed to fail in torsion. In addition, SF and PPF were used at 0%, 1%, 2%, 3% and 4%, in terms of volume. One of the beams was used as a control without fibres. Thus, experimental results on the ultimate torsional moment, angle of twist, torsional stiffness, failure modes and maximum crack width of specimens were investigated. In addition, a comparison was performed between the experimental results and ACI models, and then a new model is proposed to predict the cracking and ultimate torque of HPC beams containing various fibres contents. Experiments showed that the use of PPF and SF improved both torsional moment and angle of twist while the torsional performance of HPC beams reinforced by PPF was higher than that of those reinforced by SF. Conversely, the positive influence of SF on the torsional stiffness of HPC beams was greater than that of PPF. Therefore, the use of 4% PPF and SF improved the torsional moment strength by about 122.3% and 85.2%, respectively.